2014
DOI: 10.1248/bpb.b13-00418
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Serum Uric Acid by Difference of the Renal Protective Effects with Atorvastatin and Rosuvastatin in Chronic Kidney Disease Patients

Abstract: Hyperuricemia and hyperlipidemia have attracted attention as progression factors for chronic kidney disease (CKD). In the drug treatment of hyperuricemia and hyperlipidemia complications, Atorvastatin (ATV), which inhibits urinary protein, increases glomerular filtration rate (GFR) and has renal protective effects, and Rosuvastatin (ROS) were found be suitable because they promote serum uric acid (SUA) excretion. However, these drugs were administered at very high doses in previous studies. In this study, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…One retrospective study demonstrated a greater decrease in serum uric acid levels with atorvastatin treatment than with rosuvastatin treatment, which could lead to increased endothelial function and renal blood flow [31]. Even though we did not observe a significant difference between the serum uric acid levels in the two statin treatment groups in the current study, both statin treatments did reduce patient serum uric acid levels.…”
Section: Discussioncontrasting
confidence: 81%
“…One retrospective study demonstrated a greater decrease in serum uric acid levels with atorvastatin treatment than with rosuvastatin treatment, which could lead to increased endothelial function and renal blood flow [31]. Even though we did not observe a significant difference between the serum uric acid levels in the two statin treatment groups in the current study, both statin treatments did reduce patient serum uric acid levels.…”
Section: Discussioncontrasting
confidence: 81%
“…Atorvastatin, initially used as a modulator of hypercholesterolemia, has been recently associated with different functions, such as protection against microvascular damage, antifibrotic and anticalcifying effects; in addition, it exhibits antioxidant properties if administered in high doses for the pretreatment of lesions of the myocardium in heart failure, renal disease and abdominal surgery (35)(36)(37). These functions are due to the effect of this drug on populations of mononuclear cells, for example the subpopulations of TCD4 + lymphocytes in reciprocity with or independent from the population of cells of the mononuclear system, such as tissue macrophages, Kupffer cells in the liver, microglial cells in the central nervous system and mucosal dendritic cells (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, rosuvastatin could reduce the levels of Ox-LDL in the plasma of hemodialysis patients with end-stage renal disease (7). Rosuvastatin could control the progress of liver fibrosis by inhibiting the activity of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA), which is a key enzyme in the accumulation of cholesterol (8).…”
Section: Introductionmentioning
confidence: 99%